2019
DOI: 10.23736/s1973-9087.18.04977-8
|View full text |Cite
|
Sign up to set email alerts
|

Pain extent is more strongly associated with disability, psychological factors, and neck muscle function in people with non-traumatic versus traumatic chronic neck pain: a cross sectional study

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes. Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
5
29
2
1
Order By: Relevance
“…From the thirteen studies that were examined, two were excluded, the first one because it included asymptomatic individuals [ 11 ], and the second one because it was a randomized controlled clinical trial [ 19 ]. A total of eleven cross-sectional cohort studies [ 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were included in the final literature data mapping ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the thirteen studies that were examined, two were excluded, the first one because it included asymptomatic individuals [ 11 ], and the second one because it was a randomized controlled clinical trial [ 19 ]. A total of eleven cross-sectional cohort studies [ 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were included in the final literature data mapping ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies used digital software-based computation for calculating pain extent with six of them collecting data with digitalized PDs on a tablet [ 10 , 20 , 21 , 24 , 27 , 28 ] and five using a pen-to-paper approach [ 22 , 23 , 25 , 26 , 29 ]. Across all studies, the pain extent ranged from 6.7% to 22% (mean ± SD: 12.1% ± 5.3%), and in all cases its computation was software-based as per the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Reis et al (2018) had studied brain regions related to emotions and cognition in patients with chronic pain and found that changes in brain function are related to CWP in various regions of the body. In particular, CWP was associated with high rates of anxiety and depression, but evidence is still scarce (Hagen et al, 2011;Ris et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al noted that recent clinical guidelines universally recommend psychosocial assessment for musculoskeletal pain, with the exception of neck pain [36]. Psychological states have been shown to be significantly associated with the extent of opioid abuse [37,38]. However, recommendations based on psychological status assessment of neck pain treatment have been contradictory, showing that the effect of psychological status in neck pain patients is not well understood.…”
Section: Discussionmentioning
confidence: 99%